Damage and restoration of historical urban walls: literature review and case of studies (Fracture and Structural Integrity, 2023)
Within this work, the causes of collapses and damages occurred in masonry artefacts have been evaluated to properly identify suitable monitoring and restoration methods. In this regard, a comprehensive literature review has been performed. Based on the results, the moisture has found to be a critical parameter, which affects the structural health of masonry artefacts. Diverse non-destructive methods were employed to measure the moisture and monitor the materials involved: the Infrared Thermography, the Electrical Resistivity Tomography and the Ground Penetrating Radar, the Laser Scanning and Digital Terrestrial Photogrammetry, the Global Navigation Satellite Systems, the Unilateral Nuclear Magnetic Resonance, the Laser-Induced Fluorescence technique, the Acoustic Imaging and the Acoustic Tomography, the Geographic Information System and on-site survey process as well as computer modeling of the structure with specific FEM software. Finally, the implementation of tie-beams, Fiber Reinforced Polymers layers, ventilation, draining systems, and high-quality materials are proposed as solutions for controlling the moisture effect and retrofitting.
Keywords: Historical urban walls collapse; masonry degradation; masonry vulnerability; preservation of historical heritage.